Bacteriological Study and Antimicrobial Susceptibility Pattern in Patients with Auricular Perichondritis - Khan, Mohammad Suliman; Samad, Md Sazzad (Community Based Medical Journal, 2025)
A cross-sectional, observational study was carried out in the Department of Otolaryngology & Head-Neck Surgery, Dhaka Medical College Hospital and Department of Clinical Microbiology, ICDDR,B, Dhaka, Bangladesh, from April to September of 2019. to isolate bacteria responsible for auricular perichondritis and their antimicrobial susceptibility pattern. A total of 50 patients with auricular perichondritis were included in this study. Among 50 patients, most were (42%) in 31–45 years age group, followed by 16–30 years age group (26%). Male-female ration was 3:2. 70% of them were hailing from rural areas, while 30% were living in urbal areas. Most of them were from poor families. Among etiology, 24(48%) cases presented following road traffic accident, followed by ear piercing 7(14%), burn 5(10%) and post-surgical 4(8%). All the patients 50(100%) had pain and tenderness, followed by swelling of pinna 32(64%), fever 20(40%), disfigurement of the ear 16(32%), and discharge from ear 6(12%). 12(24%) patients had diabetes mellitus. Pseudomonas species was the commonest organism isolated 18 (36%) as single, and 8(16%) as mixed infection; 3(6%) of culture yielded no growth. The most effective antibiotic was meropenam 37(74%) followed by ceftazidime 33 (66%) and amoxiclav 32(64%). Our data suggests that the most frequently isolated organism in auricular perichondritis is Pseudomonas species, which is mostly susceptible to meropenam. CBMJ 2025 July: vol. 14 no. 02 P:81-86